Targeting ferroptosis as a potential strategy to overcome the resistance of cisplatin in oral squamous cell carcinoma - Chen, Rongkun; Zhu, Shuyu; Zhao, Ruoyu; Liu, Wang; Jin, Luxin; Ren, Xiaobin; He, Hongbing (Frontiers in Pharmacology, 2024)
Oral squamous cell carcinoma (OSCC) is a crucial public health problem, accounting for approximately 2% of all cancers globally and 90% of oral malignancies over the world.Unfortunately, despite the achievements in surgery, radiotherapy, and chemotherapy techniques over the past decades, OSCC patients still low five-year survival rate. Cisplatin, a platinum-containing drug, serves as one of the first-line chemotherapeutic agents of OSCC.However, the resistance to cisplatin significantly limits the clinical practice and is a crucial factor in tumor recurrence and metastasis after conventional treatments. Ferroptosis is an ironbased form of cell death, which is initiated by the intracellular accumulation of lipid peroxidation and reactive oxygen species (ROS). Interestingly, cisplatin-resistant OSCC cells exhibit lower level of ROS and lipid peroxidation compared to sensitive cells. The reduced ferroptosis in cisplatin resistance cells indicates the potential relationship between cisplatin resistance and ferroptosis, which is proved by recent studies showing that in colorectal cancer cells. However, the modulation pathway of ferroptosis reversing cisplatin resistance in OSCC cells still remains unclear. This article aims to concisely summarize the molecular mechanisms and evaluate the relationship between ferroptosis and cisplatin resistance OSCC cells, thereby providing novel strategies for overcoming cisplatin resistance and developing new therapeutic approaches.